2021
DOI: 10.1177/02692155211040727
|View full text |Cite
|
Sign up to set email alerts
|

Economic analysis of the ‘Take Charge’ intervention for people following stroke: Results from a randomised trial

Abstract: Objective: To undertake an economic analysis of the Take Charge intervention as part of the Taking Charge after Stroke (TaCAS) study. Design: An open, parallel-group, randomised trial comparing active and control interventions with blinded outcome assessment Setting: Community. Participants: Adults ( n = 400) discharged to community, non-institutional living following acute stroke. Interventions: The Take Charge intervention, a strengths based, self-directed rehabilitation intervention, in two doses (one or tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…40 A costeffectiveness analysis of the Taking Charge after Stroke (TaCAS) trial showed a mean cost saving of $US1412 per person treated in the first year after stroke and the cost per quality-adjusted life year gained for the Take Charge intervention was $US − 35,296 ( = £ − 25,524, € − 30,019). 41 Our hypothesis that intrinsic motivation and patient engagement are critical factors in enabling successful recovery after stroke may explain the positive results of the Stroke Unit trials. These found a substantial mortality benefit of OISC against general medical wards.…”
Section: An Alternative Hypothesismentioning
confidence: 96%
See 1 more Smart Citation
“…40 A costeffectiveness analysis of the Taking Charge after Stroke (TaCAS) trial showed a mean cost saving of $US1412 per person treated in the first year after stroke and the cost per quality-adjusted life year gained for the Take Charge intervention was $US − 35,296 ( = £ − 25,524, € − 30,019). 41 Our hypothesis that intrinsic motivation and patient engagement are critical factors in enabling successful recovery after stroke may explain the positive results of the Stroke Unit trials. These found a substantial mortality benefit of OISC against general medical wards.…”
Section: An Alternative Hypothesismentioning
confidence: 96%
“…40 A cost-effectiveness analysis of the Taking Charge after Stroke (TaCAS) trial showed a mean cost saving of $US1412 per person treated in the first year after stroke and the cost per quality-adjusted life year gained for the Take Charge intervention was $US − 35,296 ( = £ − 25,524, € − 30,019). 41…”
Section: An Alternative Hypothesismentioning
confidence: 99%